Quackery eaudiobook A brief history of the worst ways to cure everything. - Kang, Lydia (Tantor Media, 2018)
What won't we try in our quest for perfect health, beauty, and the fountain of youth? Well, just imagine a time when doctors prescribed morphine for crying infants. When liquefied gold was touted as immortality in a glass. And when strychnine—yes, that strychnine, the one used in rat poison—was dosed like Viagra. Looking back with fascination, horror, and not a little dash of dark, knowing humor, Quackery recounts the lively, at times unbelievable, history of medical misfires and malpractices. Ranging from the merely weird to the outright dangerous, here are dozens of outlandish, morbidly hilarious "treatments"—conceived by doctors and scientists, by spiritualists and snake oil salesmen (yes, they literally tried to sell snake oil)—that were predicated on a range of cluelessness, trial and error, and straight-up scams. This book seamlessly combines macabre humor with science and storytelling to reveal an important and disturbing side of the ever-evolving field of medicine.